Kajian Disparitas Perempuan dan Pembangunan Kota Surakarta - Nugraheni Dwi Hastuti; Suranti Suranti; Iik Suryati Azizah (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
The difference in roles between women and men in society has resulted in differences in the participation of women and men in the development process in Surakarta City. The participation of women is still far behind when compared to the participation of men. This can be seen from the indicators IPG (Gender Development Index), IDG (Gender Empowerment Index), TPAK (Labor Force Participation Rate), the phenomenon of feminization of poverty, and the level of women's representation in the DPRD (Regional People's Representative Council) in Surakarta. The impact is that women do not get the same benefits as men from the process or results of development in the City of Surakarta. As a result, development cannot take place optimally.